(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to identify the reality of non-performing debts in Libyan Islamic banks and methods of treatment. The study used the descriptive approach through the use of content analysis method for a set of previous studies to achieve the objectives of the study. The study reached a number of results represented in the following: factors influencing the prioritization of debt treatment, challenges facing non-performing debts, and the importance of continuous dialogue with customers and providing flexible repayment plans. The study recommends enhancing communication with customers, developing flexible repayment policies, improving risk management, using technology, encouraging innovation, and strengthening cooperation with Sharia bodies Keywords: Non-Performing Debts, Islamic Banks, Debt Treatment